Genesis of dairy based farmer producer companies in Kerala - Jose, Elizabeth; Meena, H R; Meena, B S (Indian Journal of Dairy Science, 2019)
A study on the genesis of dairy based farmer producer companies was carried out in five companies of Kerala. From each company 24 members were randomly selected. Reasons behind the formation of company were analyzed statistically. The study revealed that 96.66 percent of respondents viewed better price realization through direct sale of farm produce by eliminating middleman as the foremost reason of company formation followed by availability of farm inputs at reasonable rate (90.83%) and benefits from various government schemes (90.83%) through producer company. Other important reasons were upgraded technology, reducing risk in farming, upliftment of women, value addition, capacity building and storage facility.